Exploring Scavenging Behavior of Bobcats (Lynx rufus) in the Middle Tennessee Area and Its Forensic Implications - Yangseung Jeong; Aaron Gatewood; Eun Jin Woo (Forensic Sciences)
(1) Background: Scavenger activity can pose significant challenges in forensic investigations. When examining damage on a victim, forensic investigators must first determine whether the damage resulted from human actions or animal scavenging. Accordingly, knowledge of the scavenger populations inhabiting a specific region and their scavenging behaviors is essential for accurately reconstructing the environmental context of the remains and interpreting associated taphonomic evidence in forensic investigations. (2) Methods: This study investigates the scavenging behavior of bobcats (Lynx rufus), a species native to North America, under controlled experimental conditions. The authors placed the carcasses of seven adult white-tailed deer in an outdoor field in Murfreesboro, Tennessee, and systematically documented the scavenging activities. (3) Results: Bobcats were observed to primarily scavenge soft tissue from the torso, focusing on musculature while generally avoiding bony regions. When unsatisfied with the torso, they shifted attention to the upper limbs, with minimal interest shown in the head or neck. Bobcats also exhibited a tendency to feed in a single area for extended periods, leading to concentrated damage in specific locations on the remains. (4) Conclusions: The findings demonstrate that bobcats can significantly influence the postmortem conditions of remains, producing characteristic patterns of modification. Recognizing these patterns is essential for forensic investigators and examiners when interpreting scavenger-related alterations in forensic contexts.